Revolutionising portal hypertension diagnosis: the rise of non-invasive techniques in liver cirrhosis - Bocheng Gao; Bocheng Gao; Yumeng Lin; Huimin Zhang; Yulin Li; Yulin Li; Shuhua Gou; Shuhua Gou; Peiling Ma; Peiling Ma; Xueni Zhao; Xueni Zhao; et al. (Frontiers in Medicine)
Liver cirrhosis is associated with serious complications of portal hypertension (PH), which ultimately causes variceal bleeding and ascites in a life-threatening manner. Non-invasive diagnostic techniques have evolved as an essential tool of early detection and management from a stand point of being dependent on invasive diagnostic techniques. This review summarises the most recent progress in noninvasive diagnostic possibilities in PH in liver cirrhosis in terms of its clinical use and future outlook. A literature review within the last decade and beyond revealed such studies which developed and utilised the indexing technique such as transient elastography, shear wave elastography and other more advanced imaging modalities. Non-invasive techniques which can be used to diagnose PH and monitor it have been made and have been shown to have the possibility of obviating invasive procedures. Given that these are noninvasive techniques, they represent valuable alternatives to invasive PH testing, and future work needs to be directed towards increasing accuracy of these tests and implementing these techniques into routine clinical practise.